2019
DOI: 10.1016/j.pan.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Circulating interleukin-6 is associated with disease progression, but not cachexia in pancreatic cancer

Abstract: Background: Cachexia is a wasting syndrome characterized by involuntary loss of >5% body weight due to depletion of adipose and skeletal muscle mass. In cancer, the pro-inflammatory cytokine interleukin-6 (IL-6) is considered a mediator of cachexia and a potential biomarker, but the relationship between IL-6, weight loss, and cancer stage is unknown. In this study we sought to evaluate IL-6 as a biomarker of cancer cachexia while accounting for disease progression. Methods: We retrospectively studied 136 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 25 publications
4
36
1
Order By: Relevance
“…IL-6 is expressed within the TME lL6/IL-6 was overexpressed in human PDAC tumours in comparison with adjacent normal tissue [165,169]. Whilst this tumour-specific elevation has been correlated with reduced survival in some studies [69,155,157,161,165], others showed no significant correlation with survival [160], similar to the data available in The Cancer Genome Atlas (TCGA) dataset for both IL-6 and IL-6R ( Figure 3A,B). The TCGA comprise aggregate sequencing data, which does have limitations regarding interpretation of contributions of individual cell populations to disease outcome; however, it remains a widely used resource for exploratory investigations.…”
Section: Interleukin 6 In Pdacsupporting
confidence: 76%
See 2 more Smart Citations
“…IL-6 is expressed within the TME lL6/IL-6 was overexpressed in human PDAC tumours in comparison with adjacent normal tissue [165,169]. Whilst this tumour-specific elevation has been correlated with reduced survival in some studies [69,155,157,161,165], others showed no significant correlation with survival [160], similar to the data available in The Cancer Genome Atlas (TCGA) dataset for both IL-6 and IL-6R ( Figure 3A,B). The TCGA comprise aggregate sequencing data, which does have limitations regarding interpretation of contributions of individual cell populations to disease outcome; however, it remains a widely used resource for exploratory investigations.…”
Section: Interleukin 6 In Pdacsupporting
confidence: 76%
“…Elevation of serum IL-6 is a negative prognostic marker in human PDAC Serum IL-6 levels were increased in PDAC patients compared with healthy patients [69,[152][153][154][155][156][157][158] or those with chronic pancreatitis [152,154,157,158], and were also increased in patients with metastatic PDAC compared to those with locally advanced disease [157][158][159][160][161]. Moreover, elevated serum IL-6 positively correlated with increased disease burden, weight loss/cachexia, and metastasis [69,[152][153][154][155][156][157][158][159][160][162][163][164][165][166][167], however, there are conflicting observations in the literature regarding IL-6 and cachexia [161]. Although, increased serum IL-6 levels correlate with increased disease stage, and in metastatic patients correlates with poor overall survival [161,168].…”
Section: Interleukin 6 In Pdacmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cancer and cachexia are associated with systemic inflammation affecting multiple organ systems (Argiles et al, 2018;Onesti and Guttridge, 2014). While various cytokines, chemokines, and growth factors are changed in PDAC, Interleukin-6 (IL-6) specifically has been positively correlated with PDAC presence (Holmer et al, 2014), disease progression (Ramsey et al, 2019), mortality Suh et al, 2013), and cachexia (Okada et al, 1998) (Ebrahimi et al, 2004) (Martignoni et al, 2005). Although circulating IL-6 levels are not always detectable in early PDAC nor always correlated with cachexia severity (Ramsey et al, 2019;Talbert et al, 2018), higher tumor staining for IL-6 is associated with PDAC cachexia (Martignoni et al, 2005) and induction of monocyte IL-6 is predictive of survival in PDAC (Moses et al, 2009), suggesting that the serum levels of this short-lived cytokine might not be an appropriate measure of tissue activity.…”
Section: Introductionmentioning
confidence: 99%
“…While various cytokines, chemokines, and growth factors are changed in PDAC, Interleukin-6 (IL-6) specifically has been positively correlated with PDAC presence (Holmer et al, 2014), disease progression (Ramsey et al, 2019), mortality Suh et al, 2013), and cachexia (Okada et al, 1998) (Ebrahimi et al, 2004) (Martignoni et al, 2005). Although circulating IL-6 levels are not always detectable in early PDAC nor always correlated with cachexia severity (Ramsey et al, 2019;Talbert et al, 2018), higher tumor staining for IL-6 is associated with PDAC cachexia (Martignoni et al, 2005) and induction of monocyte IL-6 is predictive of survival in PDAC (Moses et al, 2009), suggesting that the serum levels of this short-lived cytokine might not be an appropriate measure of tissue activity. Functional data also support a role for IL-6 in PDAC tumor development (Lesina et al, 2011), progression (Zhang et al, 2013), metastasis (Razidlo et al, 2018), anti-tumor immunity (Flint et al, 2016), and response to chemotherapy (Long et al, 2017).…”
Section: Introductionmentioning
confidence: 99%